Hyperinsulinemia is Associated with Increased Soluble Insulin Receptors Release from Hepatocytes - Hiriart, Marcia; Sanchez-Soto, Carmen; Diaz-Garcia, Carlos Manlio; Castanares, Diana T.; Avitia, Morena; Velasco, Myrian; Mas-Oliva, Jaime; Macias-Silva, Marina; González-Villalpando, Clicerio; Delgado-Coello, Blanca; Sosa-Garrocho, Marcela; Vidaltamayo, Román; et al. (Frontiers in Endocrinology, 2014)
It has been generally assumed that insulin circulates freely in blood. However it can also interact with plasma proteins. Insulin receptors are located in the membrane of target cells and consist of an alpha and beta subunits with a tyrosine kinase cytoplasmic domain. The ectodomain, called soluble insulin receptor (SIR) has been found elevated in patients with diabetes mellitus. We explored if insulin binds to SIRs in circulation under physiological conditions and hypothesize that this SIR may be released by hepatocytes in response to high insulin concentrations. The presence of SIR in rat and human plasmas and the culture medium of hepatocytes was explored using Western blot analysis. A purification protocol was performed to isolated SIR using affinity, gel filtration and ion exchange chromatographies. A modified reverse hemolytic plaque assay was used to measure SIR release from cultured hepatocytes. Incubation with 1 nmol l-1 insulin induces the release of the insulin receptor ectodomains from normal rat hepatocytes. This effect can be partially prevented by blocking protease activity. Furthermore, plasma levels of SIR were higher in a model of metabolic syndrome, where rats are hyperinsulinemic. We also found increased SIR levels in hyperinsulinemic humans. SIR may be an important regulator of the amount of free insulin in circulation. In hyperinsulinemia the amount of this soluble receptor increases, this could lead to higher amounts of insulin bound to this receptor, rather than free insulin, which is the biologically active form of the hormone. This observation could enlighten the mechanisms of insulin resistance.